Factors Influencing the Management Achievement of the Chinese Students Association in Thailand - Ou, Weiyong (Technium Social Sciences Journal, 2023)
The objectives of this research were 1) to inquire about states and problems of the management of the Chinese Students Association in Thailand; key informants were selected by purposive sampling and divided into three groups consisting of 375 respondents from public higher education institutions, students from private higher education institutions, and students from higher education institutions of non-education; and an instrument used was a five-rating scale questionnaire. and standard deviation were used to analyze data and 2) to propose factors influencing the management achievement of the Chinese Students Association in Thailand. Key informants were 33 administrators, staff, and Chinese diplomatic officers participating in connoisseurship. An instrument used was a meeting record form. Content analysis and classification into issues were used to analyze data. Results of inquiring about states for the management of the Chinese Students Association in Thailand were overall at a moderate level; the problems for the management of the Chinese Students Association in Thailand were overall at a high level; and the students’ recommendations consisted of five core components. The factors influencing management achievement also consisted of five aspects.